2015
DOI: 10.1002/lary.25672
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus following treatment for sporadic Acoustic neuroma

Abstract: NA Laryngoscope, 126:1639-1643, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Retrospective data evaluating tinnitus in those presenting with VS have reported conflicting outcomes: intervention improves subjective tinnitus regardless of treatment modality, or tinnitus outcomes are independent of treatment modality. 17,18 Regarding dizziness or imbalance, previous studies have demonstrated that dizziness is a primary driver of well-being among patients with VS. Currently, several retrospective studies suggest that a subset of patients who present with dizziness may experience improvement following microsurgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective data evaluating tinnitus in those presenting with VS have reported conflicting outcomes: intervention improves subjective tinnitus regardless of treatment modality, or tinnitus outcomes are independent of treatment modality. 17,18 Regarding dizziness or imbalance, previous studies have demonstrated that dizziness is a primary driver of well-being among patients with VS. Currently, several retrospective studies suggest that a subset of patients who present with dizziness may experience improvement following microsurgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…All measurements were assessed by a senior radiologist and were checked by a senior otolaryngologist. For the tumor size criteria, we referred to the 2012 Acoustic Neuroma Association membership survey and divided the tumors into three groups by size: ≤1.5 cm, 1.6–2.5 cm and ≥2.6 cm 24 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this questionnaire may be used by clinicians and researchers to classify patients according to tinnitus severity. Nevertheless, our goal was to provide to Polish ENT centers a tool which enables the evaluation of the effectiveness of applied treatments (see, e.g., Krings et al, 2014; Folmer et al, 2015; Overdevest et al, 2015; Roland et al, 2015; Wilson et al, 2015; Fackrell et al, 2016). …”
Section: Introductionmentioning
confidence: 99%